2016
DOI: 10.1007/s00221-016-4816-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduced sensitivity for visual textures affects judgments of shape-from-shading and step-climbing behaviour in older adults

Abstract: Falls on stairs are a major hazard for older adults. Visual decline in normal aging can affect step climbing ability, altering gait and reducing toe clearance. Here we show that a loss of fine-grained visual information associated with age can affect the perception of surface undulations in patterned surfaces. We go on to show that such cues affect the limb trajectories of young adults, but due to their lack of sensitivity, not that of older adults. Interestingly neither the perceived height of a step nor cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Age‐associated changes in visual perception (Table ) also lead to various difficulties such as decreased ability to focus on near objects due to hardening of the lens (i.e., presbyopia); blurred vision due to cataracts; changes in color perception, temporal resolution, and motion perception; and a loss of fine detail (high spatial frequency) patterns . Visual function is also affected by factors such as room illumination, altered gaze patterns, and reductions to the visual field, decreased contrast sensitivity, reduced dynamic and binocular visual acuity, and reduced retinal illuminance (i.e., the ability of the pupil to dilate in low illumination), as well as impaired depth perception .…”
Section: Sensory Processing Alterations In Old Agementioning
confidence: 99%
See 1 more Smart Citation
“…Age‐associated changes in visual perception (Table ) also lead to various difficulties such as decreased ability to focus on near objects due to hardening of the lens (i.e., presbyopia); blurred vision due to cataracts; changes in color perception, temporal resolution, and motion perception; and a loss of fine detail (high spatial frequency) patterns . Visual function is also affected by factors such as room illumination, altered gaze patterns, and reductions to the visual field, decreased contrast sensitivity, reduced dynamic and binocular visual acuity, and reduced retinal illuminance (i.e., the ability of the pupil to dilate in low illumination), as well as impaired depth perception .…”
Section: Sensory Processing Alterations In Old Agementioning
confidence: 99%
“…This has been suggested to point to older adults’ over‐reliance on visual information, presumably due to the faster age‐related decline of the proprioceptive and vestibular systems . This tendency, along with the age‐related decline in visual function, often results in impaired stepping ability, balance, and gait; slower movements and reactions to stimuli; and difficulties in modifying our movements in an anticipatory manner, and these have been associated with falling, depression, and lower competence in the activities of daily living …”
Section: Sensory Processing Alterations In Old Agementioning
confidence: 99%
“…As traversing an obstacle is an action task, the focus of the current study was the resultant locomotor behaviour rather than explicit perceptual judgements. While a corresponding change in perceived obstacle height has been found alongside motor adaptations to increase foot clearance during obstacle traversal [24,25], other studies have found a dissociation between motor responses and explicit perceptual judgement in tasks for which an object's explicitly perceived size is illusorily modified [51][52][53][54][55]. Different experimental methodologies may have contributed to the differing findings, as both continuous online feedback during the task and repeated task exposure appear to facilitate motor adaptation without associated perceptual adaptation, and hence differentiation between the two metrics [24,54].…”
Section: Discussionmentioning
confidence: 99%
“…By improving the visibility of the stairs, stair users' gait can be altered to reduce the likelihood of fall. Some results of these gait alterations include increased toe clearance, increased heel clearance, faster walking speed, or reduced kinematic variance (Cohen & Sloan, 2016;den Brinker et al, 2005;David B. Elliott, Vale, Whitaker, & Buckley, 2009;Foster, Buckley, Whitaker, & Elliott, 2016;Foster et al, 2014;Jacobs, 2016;Schofield, Curzon-Jones, & Hollands, 2017;Shaheen et al, 2018;Skervin et al, 2021;Thomas et al, 2021;Zietz, Johannsen, & Hollands, 2011). In fact, Elliott, Foster and colleagues have demonstrated that vertical, monochrome striping on the face of the bottom and top steps can increase vertical foot clearance 0.8 cm for young adults and up to 2.1 cm for older adults (D. B.…”
Section: Introductionmentioning
confidence: 99%
“…Elliott, Foster, Whitaker, Scally, & Buckley, 2015; David B. Elliott, Vale, Whitaker, & Buckley, 2009; Foster, Buckley, Whitaker, & Elliott, 2016; Foster et al, 2014; Foster, Whitaker, Scally, Buckley, & Elliott, 2015; Jacobs, 2016; Schofield, Curzon-Jones, & Hollands, 2017; Shaheen et al, 2018; Skervin et al, 2021; Thomas et al, 2021; Zietz, Johannsen, & Hollands, 2011). In fact, Elliott, Foster and colleagues have demonstrated that vertical, monochrome striping on the face of the bottom and top steps can increase vertical foot clearance 0.8 cm for young adults and up to 2.1 cm for older adults (D. B.…”
Section: Introductionmentioning
confidence: 99%